Elemen Seni Bina yang Mempengaruhi Skor Pemarkahan Sistem Penilaian Kualiti QLASSIC dalam Projek Perumahan - Sarpin, Norliana; Hashim, Nur Akma Hanim; Ismayatim, Norddin (Research in Management of Technology and Business, 2020)
The success of housing projects depends on its quality performance. The QLASSIC system was introduced by CIDB in 2007 for maintaining and controlling the quality of a building. However, the dissatisfaction from buyer's with the quality of housing is still occur in the industry. This study was conducted to identify the architectural elements that influenced QLASSIC's scoring and identified strategies in improving the quality of the architectural elements. This study was conducted using a quantitative method which involve the distribution of questionnaires to developers who involved with the QLASSIC system in their housing project evaluation. The respondent of this study was developers who have been awarded QLASSIC awards in housing projects. The findings of this study show that architectural elements such as floor, wall, roof, ceiling, doors / windows, fixtures and drains are elements that influence scoring scores in QLASSIC system evaluation. Whereas, the most important strategy in improving the quality of architecture elements are include fixture element, floor element and drainage parameter element. This study is expected to assist developers and contractors to improve their construction quality in order to achieve the required quality standards in the QLASSIC system.